CCAFS science improves climate smartness of USD 334m annual coffee and cocoa investments by the Council on Smallholder Agricultural Finance - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The 11 agriculture impact investors in CSAF invest ~334m annually in coffee and cocoa with no consistent way to assess climate and deforestation risk. By combining exposure maps, gradient specific CSA practices and real-time deforestation monitoring into a web-based tool, the project helps them visualize risks. As a result they discuss appropriate strategies to mitigate risks through CSA and reduced deforestation with their 700+ clients who adapt their training, extension and support activities provided to 2.3 million smallholders globally.